KENDALA PENERAPAN PERSYARATAN TEKNIS DAN LAIK JALAN UNDANG-UNDANG LALU LINTAS DAN ANGKUTAN JALAN PADA KENDARAAN VESPA ROSOK (STUDI KASUS POLRES KABUPATEN KEDIRI) - Fatwa Azis Wicaksono (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2021)
Fatwa Azis Wicaksono, Setiawan Noerdajasakti, Solehuddin Faculty of Law Universitas Brawijaya Jl. MT. Haryono No. 169, Malang e-mail: Fatwaazis98@gmail.com  ABSTRAK Penelitian ini bertujuan untuk mengetahui secara mendalam mengenai kendala yang dihadapi dalam penerapan Persyaratan Teknis dan Laik Jalan sesuai dengan Undang-Undang Lalu Lintas dan Angkutan Jalan pada kendaraan vespa rosok. Metode ini menggunakan metode penelitian pendekatan Yuridis Sosiologi yang bertujuan untuk mengetahui pengetahuan hukum didalam kehidupan bermasyarakat. Partisipan dalam penelitian melibatkan 2 anggota Satuan Lalu Lintas (Satlantas) Polres Kabupaten Kediri di Kantor Satlantas Polres Kabupaten Kediri. Hasil penelitian mengungkapkan bahwa penindakan yang dilakukan oleh Satlantas Kabupaten Kediri telah sesuai dengan prosedur Undang-Undan Lalu Lintas dan Angkutan Jalan. Namun dalam pelaksanaannya masih dirasa kurang maksimal dalam penindakan karena dalam penindakan masih kurang meluas di daerah terluar dari Kabupaten Kediri. Sehingga permasalahan terkait vespa rosok masih belum bisa diselesaikan.Kata Kunci: Penerapan peraturan Lalu lintas dan angkutan jalan, satuan lalu lintas,  vespa rosok ABSTRACTThe traffic unit, or locally referred to as Satlantas, plays a specific role in organizing order and educating people as road users in a Sub-regional Police Department. Their role is deemed indispensable in minimizing the potential of traffic violations that can lead to road accidents resulting from factors such as drivers, riders, their precaution in riding and driving, or other factors such as environment/road. This matter is governed in Law Number 22 the Year 2009 concerning Traffic and Road Transport, especially in Article 285 Paragraph (1). This article regulates technical requirements and roadworthiness in road transports running on the road. Trashy Vespas in Kediri city are considered contravening the rules outlined in the law, and they are often seen on the road. Law enforcers of the traffic unit in the Regency of Kediri have a responsibility to settle the issue. The implementation of the law as mentioned is not optimally implemented to settle the existing issue due to the lack of introduction of the regulatory provisions to the members of the public. The introduction is not given every year, and the last introduction was given only in 2019, involving only one representative from each community. A lack of representatives has made this introduction ineffective. Implementation of fine is not enforced accordingly, and this leniency seems to allow trashy Vespas to keep operating on the road. As a consequence, this problem has persisted for more than 15 years. This research aims to investigate, describe, and analyze legal enforcement according to the regulations in the implementation of law enforcement of Article 285 Paragraph (1) of Law concerning Traffic and Road Transports regarding trashy Vespas operating on the road in the Regency of Kediri. This research employed empirical-juridical methods and was conducted in the Traffic Unit Office in the Regency of Kediri. The research results have revealed the law enforcement in the case stated has not been optimally implemented. Keywords: law enforcement, traffic unit, Law Number 22 of 2009 concerning Traffic and Road transport, trashy Vespas as transports